The Fragmentary Social-Spatial Logic and the Production of Social Housing Under the Brazilian Program “Minha Casa Minha Vida” - Nagib, Gustavo [UNESP]; Nakayama, Katia Atsumi [UNESP] (Springer Nature, 2024)
Brazilian cities have experienced transformations characterized by polycentrism, the proliferation of gated communities for high and medium-income groups, indoor shopping spaces, and a novel approach to the production of working-class space. This latter aspect, being subsidized by the State and implemented in collaboration with private real estate entities, reflects both spatial transformations and the everyday practices of urban residents. These changes significantly impact daily life, underscoring aspects of socio-spatial fragmentation. This article analyses such fragmentation in relation to the production of social housing, focusing specifically on two urban contexts in Brazil: the medium-sized city of Presidente Prudente and the metropolis of São Paulo. The research has a qualitative nature, primarily involved conducting and analysing interviews with residents of vertical gated communities from the Brazilian federal government’s housing program “Minha Casa Minha Vida”. The results indicate socio-spatial redefinitions in both urban contexts, which include changes in inhabitants’ mobility, the privatization of leisure spaces, limited integration between gated communities and their immediate surroundings, physical segregation enforced by walls and security measures, and the homogenization of the landscape.